The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1002/ana.21338
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/IItrial of MYO‐029 in adult subjects with muscular dystrophy

Abstract: This trial supports the hypothesis that systemic administration of myostatin inhibitors provides an adequate safety margin for clinical studies. Further evaluation of more potent myostatin inhibitors for stimulating muscle growth in muscular dystrophy should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
291
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 410 publications
(299 citation statements)
references
References 34 publications
2
291
0
6
Order By: Relevance
“…In effect, myostatin is a skeletal muscle-specific secreted peptide that essentially modulates myoblast proliferation and thus muscle mass/strength . Preclinical trials using myostatin loss or inhibition have been effective in ameliorating symptoms of weakness in several animal Klimek et al 2010;Bogdanovich et al 2002;Lee and McPherron 2001;Liu et al 2008;Morrison et al 2009;Murphy et al 2010;Qiao et al 2009;Siriett et al 2006;Tsuchida 2008;Wagner et al 2008;Zhu et al 2007). In humans, myostatin inhibitors, such as MYO-029, have an adequate safety margin and are able to improve the muscle strength/function or muscle contractile properties in some patients with muscular dystrophy (Krivickas et al 2009;Wagner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In effect, myostatin is a skeletal muscle-specific secreted peptide that essentially modulates myoblast proliferation and thus muscle mass/strength . Preclinical trials using myostatin loss or inhibition have been effective in ameliorating symptoms of weakness in several animal Klimek et al 2010;Bogdanovich et al 2002;Lee and McPherron 2001;Liu et al 2008;Morrison et al 2009;Murphy et al 2010;Qiao et al 2009;Siriett et al 2006;Tsuchida 2008;Wagner et al 2008;Zhu et al 2007). In humans, myostatin inhibitors, such as MYO-029, have an adequate safety margin and are able to improve the muscle strength/function or muscle contractile properties in some patients with muscular dystrophy (Krivickas et al 2009;Wagner et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical trials using myostatin loss or inhibition have been effective in ameliorating symptoms of weakness in several animal Klimek et al 2010;Bogdanovich et al 2002;Lee and McPherron 2001;Liu et al 2008;Morrison et al 2009;Murphy et al 2010;Qiao et al 2009;Siriett et al 2006;Tsuchida 2008;Wagner et al 2008;Zhu et al 2007). In humans, myostatin inhibitors, such as MYO-029, have an adequate safety margin and are able to improve the muscle strength/function or muscle contractile properties in some patients with muscular dystrophy (Krivickas et al 2009;Wagner et al 2008). All these data are consistent with the growing interest in developing therapeutic inhibitors of myostatin for use in muscle-wasting disorders such as muscular dystrophy, cachexia or ageing-related sarcopenia (Tsuchida 2008) and with the fact that myostatin inhibition is proposed as a potential intervention for frailty and sarcopenia in the elderly (Swan 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systemic treatment with myostatin inhibitors provides an adequate safety margin for clinical studies (Wagner et al 2008). Whereas Wagner et al (2008) did not show improvements in muscle strength or function, they observed that a few individuals had an increased muscle size (as measured with dual-energy radiographic absorptiometry and muscle histology), supporting the bioactivity of myostatin inhibitors.…”
Section: Introductionmentioning
confidence: 99%